Pedagogical Competency of Dance Instructors in The Training of Malay Court Dance Skills Among Upper Secondary Students at Johor National Art School - Taib Bin Saearani, Muhammad Fazli; Chan, Abdul Hamid; Abdullah, Nur Nabila Micheal Lung (Harmonia: Journal of Arts Research and Education, 2021)
Dance pedagogy is a complex and dynamic field of competency that involves various skills and self-appearance. Therefore, dance instructors must widen the scope of their competency to strengthen and improve their level. This research aimed to identify the competency of dance instructors teaching the practical subject of Malay Court Dance based on factors including the components of pedagogy, curriculum, assessment, and professionalism. The data was collected from interviews with the instructors and was analyzed through thematic analysis. The findings indicated that the instructors’ competency level development could be mapped into three dimensions, namely orientation, agent, and competency content. It was concluded that art schools in Malaysia need to develop dance instructors’ competency in terms of (1) 21st-century learning needs, (2) vertical and horizontal knowledge sharing, (3) workshop, study tour, and competition, and (4) standardization of technological development relevant for curriculum, across knowledge, practical, and feeling domains.